Feeding a Novel Trace Mineral at Lower Levels to Grazing Stocker Cattle Does Not Impair Performance - C. S. Weibert; W. R. Hollenbeck; S. B. Laudert; J. D. Kubick; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
When grazing stocker cattle on native Flint Hills pasture, optimizing growth rate is important in determining overall profitability. The correct selection of mineral supplements is an important decision that can be used to help promote overall productivity during a grazing season.
Keywords: trace minerals; stocker; grazing